Analysis of GB Virus C Markers in Families Over Three Generations - Chen, Margaret (American Society for Microbiology, 1999)
GB virus C (GBV-C) markers were analyzed in two to three generations in three families with documented vertical transmission of GBV-C. None of the maternal grandparents had GBV-C markers, whereas the male spouses had GBV-C envelope 2 antibodies. Evidence was found for intrafamilial transmission but not for GBV-C transmission over three generations.